Case Report: Management of a 10-Year-Old Patient Who Presented With Infective Endocarditis and Stanford Type A Aortic Dissection - Liang, Yanxiao; Wan, Mingzhi; Wang, Lijie; Yang, Ni; Li, Dongyu (Frontiers in Cardiovascular Medicine, 2022)
A 10-year-old girl presented with a chief complaint of cyclic vomiting since the last 12 hours and chest pain since the last 6 hours. She was diagnosed with Stanford type A aortic dissection. Intraoperatively, the aortic valve was found to be bi-lobed, and infective endocarditis associated with aortic valve perforation and rupture of the aortic sinus aneurysm，was also observed. Therefore, she underwent aortic valve replacement due to an enlarged aortic root and aortic sinus repair. The perioperative recovery was good. A large amount of bloody pericardial effusion was found in this child preoperatively. Therefore, early surgical intervention was necessary. Acute aortic dissection rarely occurs in children. There are no clinical guidelines for the management of pediatric aortic dissection. However, if a large pericardial effusion exists, emergency surgery is necessary and effective. The treatment of the valve should be based on the actual situation. It is best to give priority to valve molding, although only valve replacement is suitable for infective endocarditis.